A case of Parkinson's disease following autoimmune autonomic ganglionopathy. Issue 4 (27th March 2019) - Mitsutake, Akihiko; Matsumoto, Hideyuki; Hatano, Keiko; Higuchi, Osamu; Nakane, Shunya; Hashida, Hideji
Abstract: The patient is an 80‐year‐old man. At the age of 76, he presented with acute onset of severe orthostatic hypotension and diarrhea. Anti‐ganglionic acetylcholine receptor (anti‐gAChR) antibodies were positive, and prednisolone was effective. He was diagnosed with autoimmune autonomic ganglionopathy (AAG) based on acute onset autonomic dysfunction, positive anti‐gAChR antibodies, and efficacy of prednisolone. After the event of AAG, he gradually developed Parkinson's disease (PD). Parkinsonism is described as a complication of AAG in the previous literature. Anti‐gAChR antibodies might inhibit dopamine neurotransmission and be associated with the development of PD.